Modelling a typical hiring system as a stochastic process. - Tan, Zehuei. (2008)
This paper describes how a hiring system, in which all incoming hire requests are turned away and lost when all rental units are hired out, can be modelled as a stochastic process to reflect the stochastic nature of its hire requests and hire duration.